RETRACTED: Lead and zink in permafrost forest-steppe soils - Chimitdorzhieva Erzhena; Korsunova Tsypilma; Nimbueva Ayuna; Chimitdorzhieva Galina; Baldanov Nimbu (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001